Microcontroller-based Smart Trolly Performance Analysis - Lukmanul Khakim; Agung Diki Purnomo Aji (Westscience Press, 2024)
A shopping cart is an assisting tool in the commercial area where its function is as a temporary container for selected shopping items before the items are counted and billed. The cart becomes an indispensable tool in supermarkets. The more shopping items there are, the more energy is needed to manually push or pull the cart. This is considered not very effective in supporting consumer productivity in finding and fulfilling their needs. The aim of this research is to create a smart cart used in supermarkets, thus facilitating users in carrying shopping items. The design of the smart cart combines hardware and software. Arduino Uno serves as the main component with object detection around it using the HC-SR04 Ultrasonic Sensor and Bluetooth Module as the link between the cart and Smartphone. The cart is controlled by a smartphone using Bluetooth as the connection within a maximum range of 7m, powered by 4 DC motors and a 12V DC Battery. The maximum load capacity of this cart is 2,5 Kg. The cart's ability to detect objects is limited to a distance of <20 cm.